2008
DOI: 10.1093/brief-treatment/mhn025
|View full text |Cite
|
Sign up to set email alerts
|

Power and Control as a Framework for Practice--The Case of Intimate Partner Violence Work in Taiwan

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the author manuscript from TSpace because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In an intervention evaluation, C.-L. J. Liu and Regehr (2008) found that framing family relationships in terms of power and control was alienating to some victims of violence. Crichton-Hill (2001) While some of these foundations are applicable cross-culturally, others are less relevant to certain migrant groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In an intervention evaluation, C.-L. J. Liu and Regehr (2008) found that framing family relationships in terms of power and control was alienating to some victims of violence. Crichton-Hill (2001) While some of these foundations are applicable cross-culturally, others are less relevant to certain migrant groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Taiwanese social workers trained in Duluth interventions reported that Taiwanese cultural views on gender roles contradicted the model's Western feminist perspective, with conversations framed around gender inequality, power, control, and empowerment alienating to victims (C.-L. J. Liu & Regehr, 2008). In East Asian societies, hierarchical relationalism may promote elective participation in unequal relationships between men and women because of the functional, positive impacts of such inequality (J. H. Liu, 2014).…”
Section: The Duluth Model Of Power and Controlmentioning
confidence: 99%
See 3 more Smart Citations